ANALISIS STRUKTUR DAN KINERJA INDUSTRI FURNITUR KAYU DI KOTA PEKANBARU - Perdana Boys Andre; Iyan Yani Rita; Setiawan Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the market structure and market performance of the wood furniture industry. Sampling using the entire population of wood furniture industry with the census method of 15 respondents. The data analysis used is descriptive and quantitative analysis through the structural-behaviorperformance theoretical approach. The result: The market structure of the wood furniture industry in Pekanbaru City is an oligopoly market with the highest market share of 17.94% and the lowest market share of 3.53%. The entire wood furniture industry in Pekanbaru City has a balance in the performance of the wood furniture industry with an average of 55.87%. The highest PCM with a value of 77.5% and the lowest PCM with a value of 20%.Keywords: Small industry, Structure and Performance